RESISTENSI TOKOH AKU TERHADAP KOLONIALISME DI MUSIRAWAS DALAM NOVEL KEPUNAN KARYA BENNY ARNAS - Asri, Iit Purnama (Jurnal Penelitian Humaniora, 2020)
This study aimed to reveal the forms of resistance to colonialism of  character "I" in Musirawas in Kepunan novel by Benny Arnas. The theory used in this study is postcolonial theory. Data analysis was carried out by identifying forms of resistance identified by "I" character in Kepunan novel. The researcher described information about the resistance of the forms of mimicry, hybridity, diaspora, and ambivalence through evidences in the form of quotations. I addition, the researcher interpreted the resistance done by "I" character to the Dutch colonial government in Musirawas in the field of education. The result indicated that "I" character had a critical attitude towards discrimination of the Dutch colonial government in the field of education. "I" character had a critical attitude, that was, her awareness of having the same rights as the Dutch colonial. "I" character was against the Dutch colonial government in terms of intellectuality that needed to be honored. Intellectuality helped "I" character to gain the independence from the Dutch colony.